Benign Chondroid Syringoma: Atypical Presentation of a Rare Eccrine Tumor - TEZEL, ERDEM (ELSEVIER SCIENCE INC, 2011)
Chondroid syringoma is a rare eccrine tumor that is often benign but has the potential for malignant transformation and distant metastasis. Histopathological analysis may not be definitive, and any patient with atypical features, an accelerated clinical course, or high suspicion for malignant transformation is a candidate for immediate surgical intervention and close follow-up. The purpose of this article is to review the clinical features of this rare tumor with a special emphasis on its atypical presentation. (C) 2011 by the American College of Foot and Ankle Surgeons. All rights reserved.
Keywords: foot; mixed tumor; neoplasm; surgery; sweat gland; toe